Pengaruh Kualitas Pelayanan E-Commerce Shopee Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian - Ridha Nurakhmawati; Ami Purnamawati; Indra Fahmi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Cultural acculturation with a touch of technology is one of the phenomena driving changes in human life causing the emergence of electronic commerce. One of the most popular e-commerce sites is Shopee. Shopee has many users although in terms of their satisfaction, other e-commerces come first. Buyers will be satisfied after the purchase depending on the performance offered in relation to the buyer's expectations. So, the factor that affects e-satisfaction is e-service quality through purchase decisions. The method used in this research is a quantitative method. Using purposive sampling and quota sampling techniques due to the unknown population, the researchers obtained 143 respondents as the samples. The measuring instrument used was an open and closed questionnaire with a total of 26 statements and distributed via Google Form. The data analysis technique used path analysis and SPSS version 23 software. The research result shows that E-service quality has a significant indirect effect on E-satisfaction through commerce consumer purchasing decisions. The managerial efforts to improve e-service quality and customer satisfaction as an online buyer through purchasing decisions are identifying Shopee consumers more deeply from consumer behavior, improving Shopee features, and increasing purchasing decisions because it can potentially support the effect of service quality on Shopee customer satisfaction.